Multi-component self-assembled molecular-electronic films: towards new high-performance thermoelectric systems. Issue 18 (21st April 2022) - Bennett, Troy L. R.; Alshammari, Majed; Au-Yong, Sophie; Almutlg, Ahmad; Wang, Xintai; Wilkinson, Luke A.; Albrecht, Tim; Jarvis, Samuel P.; Cohen, Lesley F.; Ismael, Ali; Lambert, Colin J.; Robinson, Benjamin J.; et al.
Abstract : Through an experimental and theoretical study, cross-plane thermoelectricity in Self-Assembled Monolayers (SAMs) was enhanced by adding extra molecular layers, presenting a new strategy towards the design of high thermoelectric materials. Abstract : The thermoelectric properties of parallel arrays of organic molecules on a surface offer the potential for large-area, flexible, solution processed, energy harvesting thin-films, whose room-temperature transport properties are controlled by quantum interference (QI). Recently, it has been demonstrated that constructive QI (CQI) can be translated from single molecules to self-assembled monolayers (SAMs), boosting both electrical conductivities and Seebeck coefficients. However, these CQI-enhanced systems are limited by rigid coupling of the component molecules to metallic electrodes, preventing the introduction of additional layers which would be advantageous for their further development. These rigid couplings also limit our ability to suppress the transport of phonons through these systems, which could act to boost their thermoelectric output, without comprising on their impressive electronic features. Here, through a combined experimental and theoretical study, we show that cross-plane thermoelectricity in SAMs can be enhanced by incorporating extra molecular layers. We utilize a bottom-up approach to assemble multi-component thin-films that combine a rigid, highly conductive 'sticky'-linker, formed from alkynyl-functionalised anthracenes, and a 'slippery'-linker consisting of a functionalized metalloporphyrin. Starting from an anthracene-based SAM, we demonstrate that subsequent addition of either a porphyrin layer or a graphene layer increases the Seebeck coefficient, and addition of both porphyrin and graphene leads to a further boost in their Seebeck coefficients. This demonstration of Seebeck-enhanced multi-component SAMs is the first of its kind and presents a new strategy towards the design of thin-film thermoelectric materials.